Exploring the feasibility of Europe's renewable expansion plans based on their profitability in the market. (June 2023) - Finke, Jonas; Bertsch, Valentin; Di Cosmo, Valeria
Abstract: Different policies aim at transforming the European energy sector. To support decision making in this context, energy system models with a central-planning approach are frequently used. However, private sector investments are required to realise the transformation and there is a shift towards more market revenue-based paradigms. Therefore, we assess the market-based profitability of renewables in 2030 across Europe under current policies, in particular renewable share targets. As several key assumptions drive the system design and profitability likewise, we perform an endogenous expansion planning to obtain a European least-cost electricity system for 2030 and shadow electricity prices to determine internal rates of return and net present values. We find that the profitability of solar PV, on- and offshore wind varies significantly across Europe, mainly driven by market values, financial and natural resource conditions. In a least-cost system enforced to fulfil national targets, renewables are mostly not profitable. Renewable expansion driven by an appropriate CO 2 price allows for exceeding the EU-wide renewable target of 65 % and achieving internal rates of return at or above the costs of capital. Therefore, policy action is required to achieve climate goals, e.g. by moving towards EU-wide renewable targets, market-based policy instruments or providing additional revenue sources. Graphical abstract: Highlights: Optimised European power system in 2030 based on renewable targets. Profitability of solar PV, onshore and offshore wind compared across Europe. With national targets, renewable investments are mostly not profitable in the market. Profitability driven by political, financial, market and natural conditions. Given renewable targets, carbon emissions differ greatly driven by CO 2 and gas prices.